A comparative study of two separation methods to isolate monocytes. Issue 2 (31st October 2018) - Weiss, Ronald; Gerdes, Wilhelm; Leonhardt, Franziska; Berthold, Rommy; Sack, Ulrich; Grahnert, Anja
Abstract: Separation of specific blood cells is necessary for a deeper insight into their role in health and disease. To obtain such cells, efficient and robust isolation methods are needed. We compare here the Fab‐based Traceless Affinity Cell Selection (TACS®) technology and the Magnetic Activated Cell Sorting (MACS®) technology to isolate human monocytes from whole blood and buffy coats as well as the differentiation of the isolated monocytes to dendritic cells (DCs). TACS® is a positive selection technology using immune affinity chromatography based on CD‐specific low affinity Fab‐fragments for the reversible capture and release of target cells. The positive selection by MACS® is based on magnetic beads coated with specific high affinity monoclonal antibodies to catch the target cells. The target cells separated by TACS® are "label‐free" while cells positively isolated by MACS® will carry the cell specific label. Our data show that the separation methods described here are well suited to obtain functional monocytes of high quality and purity. A differentiation of the cells into DCs leads to comparable results with the exception that CD1a expression levels on immature and mature DCs are elevated when monocytes are isolated using the TACS® technology. Taken together, our results suggest that the TACS® method may be of advantage when preparing monocytes and monocyte‐derived DCs for functional analyses, while the MACS® method seems to be capable of higher monocyte recoveries. © 2018 International Society for Advancement of Cytometry Abstract :